1974
DOI: 10.1002/chin.197428167
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: ORGANIC PHOTOCHEMISTRY PART 12, THE PHOTODIMERIZATION AND PHOTOISOMERIZATION OF 2‐PYRIDONE AND ITS MONOCHLORO DERIVATIVES

Abstract: Die Bestrahlung des Pyridons (I) in wäßriger Lösung liefert das Dimere (II) und das Valenzisomere (III) in einem von der Konzentration abhängenden Produktverhältnis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…e. Cycloadditions of 2-Pyridones. Intermolecular photodimerization of 2-pyridones 113 to give stereoisomeric dimers of type 114 and 115 via head-to-head and head-to-tail [4 + 4]-cycloadditions, respectively, is known for quite some time , and constitutes a useful route to cyclooctanoids, Scheme . This theme has been further elaborated by several groups, and many structural variations have been explored.…”
Section: [4 + 4]-cycloadditionsmentioning
confidence: 99%
“…e. Cycloadditions of 2-Pyridones. Intermolecular photodimerization of 2-pyridones 113 to give stereoisomeric dimers of type 114 and 115 via head-to-head and head-to-tail [4 + 4]-cycloadditions, respectively, is known for quite some time , and constitutes a useful route to cyclooctanoids, Scheme . This theme has been further elaborated by several groups, and many structural variations have been explored.…”
Section: [4 + 4]-cycloadditionsmentioning
confidence: 99%
“…Sharp and Hammond16 demonstrated that a short-lived singlet excited state is responsible for the [4 + 4] reaction, and estimated that the lifetime for this intermediate was less than 200 ps. Several reports have shown that this photodimerization is compatible with chlorine and alkylpyridone substituents, [16][17] with only 6-chloro18 or 4-alkoxy19 substitution unsuitable for the transformation. Only one other study of the intramolecular photochemistry of two pyridones has been reported, Nakamura's triplet-sensitized photoreactions of NJN'polymethylene bis(pyridones) (Figure 1), where the tether constraints combined with photosensitization produced only [2 + 2] and [4 + 2] photoproducts such as 4 and 5.20…”
mentioning
confidence: 95%
“…We were also impressed by the absence of reports concerning the chemistry of this photodimerization product, outside of the patented work of Paquette and Slomp at Upjohn. [13][14][15][16][17][18][19][20][21][22] Our initial investigations21 demonstrated that the reaction was compatible with both threeand four-carbon tether lengths. These intramolecular reactions can be run to complete conversion, whereas the intermolecular reaction requires high concentrations (>0.1 M) for [4 + 4] dimerization and unimolecular photoprocesses become significant as concentrations fall below this level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Secondly, photoreaction of 3b and 3c is strongly controlled so as to proceed in the [2 + 2] manner by the crystalline lattice of the inclusion complex. This is also an interesting result, since photoirradiation of 3b in EtOH for 20 h gave the [4 + 4] trans-anti-dimer 8b in 42% yield, 3 and since photoirradiation of 3b in EtOH containing a half molar amount of 5 also gave 8b. Reaction of 3c in solution gave the similar product, 8c.…”
mentioning
confidence: 71%